2019
DOI: 10.1371/journal.pone.0222518
|View full text |Cite|
|
Sign up to set email alerts
|

Meaningful work and resilience among teachers: The mediating role of work engagement and job crafting

Abstract: Research in the field of work and organizational psychology more and more highlights the importance of employees’ experience of meaningful work. Adding to this area of research, the present study among teachers examined the relationship between meaningful work and resilience and tested whether this proposed relationship is mediated by teachers’ work engagement and job crafting behaviour. Data for this study was collected among a group of Dutch teachers working in a school for primary education (N = 174). To te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 58 publications
6
45
0
6
Order By: Relevance
“…A study conducted among Dutch teachers found a relationship between the validation of personal work with higher determination, flexibility and better results [ 24 ]. Meanwhile, an online survey of 1278 Canadian teachers seeking to understand the association between burnout and resilience during the COVID-19 pandemic found that family support, exercise, healthy eating and emotional self-care (such as meditation and mindfulness) were the most protective variables [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted among Dutch teachers found a relationship between the validation of personal work with higher determination, flexibility and better results [ 24 ]. Meanwhile, an online survey of 1278 Canadian teachers seeking to understand the association between burnout and resilience during the COVID-19 pandemic found that family support, exercise, healthy eating and emotional self-care (such as meditation and mindfulness) were the most protective variables [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, individuals are likely to experience positive outcomes such as work engagement. Van Wingerden and Poell (2019) argued that engaged employees craft their jobs to create a better suiting and more challenging work environment. Creating a resourceful and challenging work environment leads to positive outcomes such as resilience (Van Wingerden & Poell, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…When experiencing burnout, spiritual teachers may resort to their spiritual resources, which could be related to spiritual coping or meaning-making processes that help dissipate the burnout symptoms over time (Scherer et al 2016). A deep sense of meaning and purpose in life provided by teaching may enhance teachers' resilience and willingness to combat tough situations in the workplace and not resign from their job even despite adverse consequences of burnout (Van Wingerden and Poell 2019). Spirituality at work also helps create meaning and purpose in the work, promoting motivation and engagement (Fouché et al 2017;Van Wingerden and Van der Stoep 2018), in this way potentially mitigating the relationship between burnout and turnover intention.…”
Section: Discussionmentioning
confidence: 99%